Analysis of the Instagram Account @APDCIndonesia as a Mental Health Campaign Platform - Maharani, Pramegista Dewanti; Rochmania, Ainur (Universitas Muhammadiyah Sidoarjo, 2024)
As awareness of the importance of mental health increases, social media platforms such as Instagram have become effective channels for spreading information and providing mental health support. One account that stands out in providing mental health services on Instagram is @APDCIndonesia. This study aims to analyze the content of mental health campaigns posted by @APDCIndonesia account at certain periods. This study uses Social Media theory as an analytical framework to gain in-depth knowledge about the content of mental health campaigns posted by the Instagram account @APDCIndonesia. This research uses a qualitative descriptive approach with an emphasis on literature research. The analysis process includes observing the content campaign strategy, the content presented, and the selection of content that is considered representative to be analyized. The data analysis technique used refers to the Miles and Huberman models. Based on the results, researchers found that the @APDCIndonesia Instagram account has successfully utilized social media to reach a wide and diverse audiences, increasing awareness and support for mental health, showing that with the right strategy, social media can be a very effective tool in mental health campaigns.